Beyond Weight Loss: Rethinking Treatment Strategies for Obesity - Buckley, Rita (MD Conference Express, 2012)
Can physical activity with little or no weight loss deliver health benefits? This article discusses this question and discussed the role of physical activity/exercise in the management of abdominal obesity.